Caso Hematológico - Nascimento,Patrícia (2010)
The authors present the case of a child with complex congenital heart defect, bilateral malformation of the thumbs, hearing loss, failure to thrive and delayed psychomotor development, oriented to the hematology consultation at the age of 9 years for the presence of thrombocytopenia and macrocytosis.